Proceedings of the International Conference of Social Science 2019
DOI: 10.4108/eai.21-9-2018.2281185
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Sea-Based Blended Learning eBook on The Subject of Cookies and Candies

Abstract: Utilization of smartphones that have not been maximized in education is inversely proportional to lifestyle. Therefore, the need for a learning media that can be applied to the smartphone. As a distance learning solution through digital sea learning. This study aims to determine the effectiveness of learning using eBook. The research method used quasi-experiment with pre-test and post-test design. Research subjects are 70 students of Home Economic Education who follow cookies and candies. Validity test using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…In this study, the students have the attitude to learn independently. This is in line with several other studies where the results of the analysis of students' needs have obtained a lack of innovative learning resources [11], [15]. The lack of learning resources makes lecturers never provide digital-based media on learning.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, the students have the attitude to learn independently. This is in line with several other studies where the results of the analysis of students' needs have obtained a lack of innovative learning resources [11], [15]. The lack of learning resources makes lecturers never provide digital-based media on learning.…”
Section: Resultssupporting
confidence: 88%
“…In addition, the media can help students understand the materials well. This understanding can be assessed by increasing students' learning outcomes [15]. This increase is marked by the ease of access to learning through smartphones and laptops [18].…”
Section: Subtitles and Materials About England Laminationmentioning
confidence: 99%
“…The result in the experimental group is similar to the results of previous studies. The study by Sari & Mariah (2019) found that the use of sea-based digital learning eBook increased learning outcomes on the subject Cookies and Candies. Asrowi et al (2019) also concluded that interactive e-book is effective to be used to improve the students' knowledge of the social subject in the seventh class.…”
Section: Resultsmentioning
confidence: 99%